Evaluation of harvesting time and standardization of distillation duration for higher essential oil content and quality in German chamomile (Chamomilla recutita L.) - Kumar, D.; Suryavanshi, P.; Padalia, R. C.; Chauhan, A.; Venkatesha, K. T.; Tiwari, A. K.; Singh, V. R.; Singh, S.; Upadhyay, R. K. (Journal of Spices and Aromatic Crops, 2021)
Essential oil yield and composition in aromatic crops might be affected by genetic, agronomical and environmental factors but till date there is no clear information about the harvesting time and distillation for higher essential oil content without affecting quality. The current study was carried out to evaluate harvesting of chamomile flowers without herb and with herb part at three different times (6 A.M., 12 P.M. and 6 P.M.) and four distillation treatments (3 h, 4 h, 5 h & 6 h) for dried chamomile flowers. Results indicated that essential oil content was more in chamomile flowers without herb (0.15-0.18%) as compared to flowers with herb (0.06-0.09%). Essential oil content in chamomile flowers without herb was found statistically at par at harvest time of 12 P.M. (0.18%) and 6 P.M. (0.18%) and significantly higher than harvesting time of 6 A.M. (0.15%). Essential oil of chamomile flowers without herb contained maximum α-bisabolol oxide-B, (Z)-spiroether, and chamazulene at 12 P.M. and 6 P.M. while, α-bisabolone oxide-A and α-bisabolol oxide-A were maximum at 6 A.M. and (E)-β-farnesene was more at 12 P.M. Similarly, in distillation experiment, higher oil content was observed in chamomile dried flowers which were hydro-distilled for 6 h (1.20%) compared to other hydro-distillation durations. Marker compounds i.e. α-bisabolol oxide-A, α-bisabolone oxide-A, α-bisabolol oxide-B, (E)-β-farnesene and chamazulene were more at 5 h and 6 h distillation duration while (Z)-spiroether was more at 3 h distillation duration. The present study showed that in order to obtain higher essential oil, flowers without herb harvested at 12 P.M or 6 P.M. should be subjected to 5-6 h hydro-distillation.